Q. 1 A3.9( 20 Votes )

Expand

(k + 4)3

Answer :

(k + 4)3 =(k)3 + [ 3 ×(k)2 ×(4)] + [ 3 ×(k)×(4)2 ] +(4)3


{ (a + b)3 = a3 + 3a2b + 3ab2 + b3


Here a = k, b = 4 }


= k3 +(3 × 4)k2 +(3 × 16)k + 64


= k3 + 12k2 + 48k + 64


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
RELATED QUESTIONS :

Expand

(52)3

MHB - Mathematics (New)

Expand

MHB - Mathematics (New)

Expand

(198)3

MHB - Mathematics (New)

Expand

MHB - Mathematics (New)

Expand

(101)3

MHB - Mathematics (New)

Expand

MHB - Mathematics (New)

Expand

MHB - Mathematics (New)

Simplify

(4a – 3)3 –(4a + 3)3

MHB - Mathematics (New)

Simplify

(3r – 2k)3 +(3r + 2k)3

MHB - Mathematics (New)

Simplify

(2a + b)3 –(2a – b)3

MHB - Mathematics (New)